EU civilian crisis management : the record so far - Chivvis, Christopher S. (Rand Corporation monograph series, 2010)
"The European Union has been deploying civilians in conflict and postconflict stabilization missions since 2003, and the scope of civilian missions is likely to increase in the future. This volume offers a general overview and assessment of the EU's civilian operations to date, as well as a more in-depth look at the two missions in which the EU has worked alongside NATO: the EU police-training mission in Afghanistan and the integrated rule of law mission in Kosovo. The author concludes with a discussion of the main policy implications for the United States and Europe."--Rand web site